Microseismic assessment and fault characterization at the Sulcis (South-Western Sardinia) field laboratory. (April 2020) - Anselmi, M.; Saccorotti, G.; Piccinini, D.; Giunchi, C.; Paratore, M.; De Gori, P.; Buttinelli, M.; Maggio, E.; Plaisant, A.; Chiarabba, C.
Highlights: Background Seismic baseline assessment in SW Sardinia and Sulcis basin area. Background Seismic baseline assessment in the Fault Lab area, where the methods and instruments for CCUS technologies will be developed and tested. Ambient noise tomography (ANT) technique is used to detect and delineate a shallow fault underneath the Fault Lab area. Abstract: The general acceptance of the CO2 geological storage by stakeholders passes through the assessment and mitigation of risks, potentially induced or increased by the disposal activity. Injection of moderate to large quantities of CO2 in the sub-surface may unbalance local stress and trigger earthquakes if faults are critically stressed, condition that is not easily verifiable. Pilot sites are therefore the best way to proceed further in order to address such challenging issues. In such cases, the reconnaissance of faults and seismicity in the sub-surface, before the onset of activity, is mandatory. In this paper, we present studies carried out in the site where the Sotacarbo Fault Lab is going to be installed. This facility will be located in a very low seismic hazard region of central Mediterranean, where reports on historical large earthquakes are poor. We show results from a series of experiments aimed to monitor the background seismicity around the pilot site. As expected, seismicity is almost absent down to small magnitude close to the future injection-test well. Further seismic imaging of the sub-surface layers obtained by ambient noise tomography offers the ability to resolve the presence of a seismicity-free fault located in the first 200 m below the surface, of which the last episode of activity is difficult to assess. Our results encourage the use of this site to follow the response of the system to injection of small quantity of CO2 .